The small GTP-binding proteins AgRho2 and AgRho5 regulate tip-branching, maintenance of the growth axis and actin-ring-integrity in the filamentous fungus Ashbya gossypii. - Doris Nordmann (Public Library of Science (PLoS), 2014)
GTPases of the Rho family are important molecular switches that regulate many basic cellular processes. The function of the Rho2 and Rho5 proteins from Saccharomyces cerevisiae and of their homologs in other species is poorly understood. Here, we report on the analysis of the AgRho2 and AgRho5 proteins of the filamentous fungus Ashbya gossypii. In contrast to S. cerevisiae mutants of both encoding genes displayed a strong morphological phenotype. The Agrho2 mutants showed defects in tip-branching, while Agrho5 mutants had a significantly decreased growth rate and failed to maintain their growth axis. In addition, the Agrho5 mutants had highly defective actin rings at septation sites. We also found that a deletion mutant of a putative GDP-GTP-exchange factor (GEF) that was homologous to a Rac-GEF from other species phenocopied the Agrho5 mutant, suggesting that both proteins act in the same pathway, but the AgRho5 protein has acquired functions that are fulfilled by Rac-proteins in other species.